The benevolent dictatorship: prejudice disguised as science - da S. Ruellas , Eloísio Alexsandro (Brazilian Journal of Health and Biomedical Sciences, 2025)
This editorial invites reflection on how contemporary science—especially in the biomedical field—can sometimes operate as a “benevolent dictatorship,” where moralism is disguised by a veneer of neutrality and technical language. Protocols, reports, and consensuses often claim objectivity, yet may perpetuate historical and social biases by ignoring context and complexity. Human experiences risk being reduced to rigid categories, and questioning is discouraged in favor of supposed certainty. We caution against the transformation of science into dogma and call for a scientific practice grounded in critical inquiry, humility, and openness to diverse perspectives. Science must not be a tool for control, but a means to expand understanding with ethical responsibility.